Discrete lot streaming in two-machine flow shops - Chen, Jiang; Steiner, George; McMaster University, Michael G. DeGroote School of Business (My University, 1995)
Lot streaming is the process of splitting a job or lot to allow overlapping between successive operations in a multistage production system. This use of transfer lots usually results in a substantially shorter makespan for the corresponding schedule. In this paper, we study the discrete version of the two machine flowshop problem to minimize the makespan. We present new insights into the structure of optimal schedules, which lead to a strongly polynomial solution for the problem.
22 leaves ; Includes bibliographical references (leaves 20-22). ; "April, 1995." ;
This research was supported in part by the Natural Sciences and Engineering Research Council of Canada under Grant No.OGP0001798.
Keywords: Business; Business; Production scheduling > Mathematical models Programming (Mathematics)